Dasatinib for the treatment of chronic myeloid leukemia: patient selection and special considerations - Keskin D; Sadri S; Eskazan AE (Dove Medical Press, 2016)
Dilek Keskin, Sevil Sadri, Ahmet Emre Eskazan Department of Internal Medicine, Division of Hematology, Cerrahpasa Faculty of Medicine, Istanbul University, Istanbul, Turkey Abstract: Dasatinib is one of the second-generation tyrosine kinase inhibitors used in imatinib resistance and/or intolerance, as well as in the frontline setting in patients with chronic myeloid leukemia-chronic phase, and also in patients with advanced disease. It is also utilized in Philadelphia chromosome-positive acute lymphocytic leukemia. While choosing the appropriate tyrosine kinase inhibitor (ie, dasatinib) for each individual patient, comorbidities and BCR-ABL1 kinase domain mutations should always be taken into consideration, among other things. This review mainly focuses on patient selection prior to dasatinib administration in the treatment of chronic myeloid leukemia. Keywords: chronic myeloid leukemia, comorbidity, dasatinib, mutation, tyrosine kinase inhibitor